Implementasi Kurikulum Merdeka pada Pembelajaran PAI di SMK Al Bukhary Rantau Prapat - Harahap, Ismayani; Budiman, Syahrul; Harahap, Nurhanna (MODELING: Jurnal Program Studi PGMI, 2024)
This study aims to analyze the implementation of the Merdeka Curriculum in Islamic Religious Education (PAI) learning at SMK Al Bukhary Rantau Prapat. The Merdeka Curriculum is an innovation that provides flexibility for educational institutions to develop learning methods relevant to students' needs. This research employs a descriptive qualitative method with data collection techniques including observation, interviews, and documentation. Data validity is tested using triangulation techniques. The findings indicate that the implementation of the Merdeka Curriculum in PAI learning at SMK Al Bukhary Rantau Prapat has undergone significant changes through a project-based learning approach and differentiated learning, which emphasize not only cognitive aspects but also affective and psychomotor aspects. The main challenges in implementing this curriculum include limited facilities and infrastructure, teachers’ readiness to adapt to new approaches, variations in students' abilities and motivation, and lack of parental involvement in supporting learning. Despite these challenges, the Merdeka Curriculum has had a positive impact on enhancing teachers' creativity in teaching and fostering students' character development in alignment with the Profile of Pancasila Students. This study recommends the need for collaboration among all stakeholders to create more contextual, applicable, and relevant PAI learning that meets the demands of the modern era.